Early Outcomes of Intramedullary Interlocking Nail in Closed Tibial Diaphyseal Fractures - Zarar, Musaib; Farooq, Muhammad Annam; Gul, Shakeel; Javed, Muhammad Imran; Mehmood Khan, Kashif; Ali, Pervaiz (Journal of Liaquat University of Medical & Health Sciences, 2025)
Objective: To evaluate the early outcome of intramedullary interlocking nailing in closed tibial diaphyseal fractures within the Pakistani population. Methodology: This Prospective descriptive study was conducted from April to October 2019 at the Department of Orthopedics, Jinnah Postgraduate Medical Centre, Karachi. A total of 81 patients aged 25–65 years with tibial diaphyseal fractures of either gender were included. Patients with ipsilateral femur fractures, chronic renal failure, and chronic liver disease were excluded. A consultant orthopedic surgeon performed intramedullary interlocking nailing. Postoperatively, all patients were prescribed co-amoxiclav 1 g and diclofenac sodium twice daily for two weeks. Patients were followed fortnightly for 3 months, and outcomes were assessed as excellent, good, fair, or poor according to operational definitions. The data were analyzed using SPSS version 20.0. Categorical data are presented as percentages and of numerical means. Excellent outcome associations are portrayed using Chi-square, and a p-value of <0.05 was considered significant. Results: The mean age was 38.83 ± 7.83 years, with 66 (81.48%) patients aged 25–45 years. The male-to-female ratio was 3:1, with 61 (75.31%) males and 20 (24.69%) females. Outcomes showed that 62 (76.54%) patients achieved excellent results, 8 (9.88%) had good results, 9 (11.11%) had fair results, and 2 (2.47%) had poor results. No significant association was observed between participant characteristics and the clinical outcome of patients with IMN for closed tibial fractures. Conclusion: Intramedullary interlocking nail demonstrated a high rate of excellent outcomes in the management of close tibial diaphyseal fractures.